Guibert, lecteur amoureux et «frère d'écriture» d'Eugène Savitzkaya - Almeida, José Domingues de (2012)
One of Hervé Guiberts life as well as work aspect, less known, is related to his social and literary friendship and frequentation of Eugène Savitzkaya, who was still by then a young Minuit writer, with crossed Slav origins, but whose writing and poetic work, quite unprecedented, was already recognized by Paris and Belgium. As a matter of fact, we will suggest a refreshed reading of this Savitzkayas literary phase through his friendship, or even passion to that heterosexual writer, expressed in Guibert famous « Lettre à un frère décriture ». We propose a new approach of these two writers self-fictional work and novelistic strategies.